The American genus Dactuliothrips (Thysanoptera: Aeolothripidae) with three new species - Pereyra, Veronica Valeria; De Borbon, Carlos Manuel (Magnolia Press, 2018)
Three new species of Dactuliothrips Moulton are described, two from Mendoza, Argentina and one from Southern California, USA: D. prosopis sp.n. from Prosopis alpataco (Fabaceae), D. monttea sp.n. from Monttea aphylla (Scrophulariaceae), and D. ephedra sp.n. from Ephedra sp. (Ephedraceae). A revised diagnosis and an illustrated identification key to the nine recognized species of Dactuliothrips are also provided. Pictures and notes about the host plants for the species from Argentina are included, together with new records for D. kaszabi from Argentina.